Implementation of Computational Thinking in Data Structure Subject Using Problem-based Learning Models - Rafli, Muhammad; Sutarno, Heri; Wihardi, Yaya (Jurnal Guru Komputer, 2023)
Computational thinking skills are one of the skills required in the 21st century. Computational thinking can teach students to think logically, critically, and use appropriate and efficient strategies in solving problems. However, computational thinking skills require an appropriate learning approach. Learning process must be designed to hone problem-solving skills and to acquire essential knowledge and concepts of the subject matter. This study aims to develop a computational approach media with thinking and problem-based learning and to improve students cognitive. This study uses a Comprehensive Life Cycle (SHM) methodology to develop the media. One-group pretest-postest was used for the research design. Media with computational thinking and problem-based learning approach have been developed and has obtained a score of 90% or "Very Good" by experts on media testing and get a percentage score of 92% or "Very Good" by experts on material testing. The use of media with Computational Thinking and problem-based learning approach can improve student cognitive with an increase in the average N-gain of students by 0.42 which is in the "Medium" category.  On the other hand, student responses to the learning media resulted in a score of 84%.